2021
DOI: 10.3390/ma14206106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Machining Hardened Steel AISI 4140 with Self-Propelled Rotary Tools

Abstract: It is necessary to improve the machinability of difficult-to-cut materials such as hardened steel, nickel-based alloys, and titanium alloys as these materials offer superior properties such as chemical stability, corrosion resistance, and high strength to weight ratio, making them indispensable for many applications. Machining with self-propelled rotary tools (SPRT) is considered one of the promising techniques used to provide proper tool life even under dry conditions. In this work, an attempt has been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This can influence the resulting machined surface. Compared to self-propelled technology, this monolithic tool reduces the surface roughness of the machined surface Rz by 18 μm [ 25 ] and the value of Ra parameter is stabilised and less than 0.56–1.83 μm, which was achieved in other research [ 14 ]. With ADRT technology and the use of a multi-component tool, the roughness Rz 8 μm [ 7 ] was achieved, which is a higher value compared to the highest value measured after turning with the monolith rotary tool.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This can influence the resulting machined surface. Compared to self-propelled technology, this monolithic tool reduces the surface roughness of the machined surface Rz by 18 μm [ 25 ] and the value of Ra parameter is stabilised and less than 0.56–1.83 μm, which was achieved in other research [ 14 ]. With ADRT technology and the use of a multi-component tool, the roughness Rz 8 μm [ 7 ] was achieved, which is a higher value compared to the highest value measured after turning with the monolith rotary tool.…”
Section: Discussionmentioning
confidence: 86%
“…In forced rotation, this angle does not fundamentally affect the rotational speed of the tool, as it is provided by an external drive unit. For a correct setting, it is necessary to investigate λs, since at certain values, there can be a critical increase in cutting force [ 13 , 14 ]. High temperatures are generated at the cutting point when machining materials and overall high cutting forces are generated [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The machining force components and temperature of the 51200 hardened steel were precisely predicted using a simulation model [12]. Ahmed et al pointed out that the Ra of 0.38 μm and the tool wear of 2.42 μm could be obtained using optimal parameters for rotary turning AISI 4140 steel [13]. Nieslony et al revealed that a higher V in the rotary turning process caused a decreased Ra and stable machining [14].…”
Section: Introductionmentioning
confidence: 99%
“…When turning with a conventional tool, a high temperature is generated at the cutting point due to the fact that only one point of the tool is in constant contact, and wear is concentrated at this point as well. Rotary tool machining technology leads to increased material removal, reduced cutting tool wear [ 18 , 19 ], high cooling capacity [ 8 , 20 ], extended tool life [ 21 ], and better integrity of the machined surface. The rotary tool design might be monolithic or consist of a circular cutting insert clamped in a holder that rotates freely around its axis and serves as a continuous cutting edge along its entire circumference [ 22 ].…”
Section: Introductionmentioning
confidence: 99%